A study of Obstructive Uropathy among Children - Shivani Pandey; Sukant Pandey (Asian Journal of Clinical Pediatrics and Neonatology, 2014)
Background: Where within the infection occur repeatedly deed residual inflammatory changes. it's additional common within the presence of structural or useful anomalies of the tract, that interfere with drain of piddle. Common organisms area unit E. coli in early infancy, whereas the later resistant organism like proteus and enteric bacteria predominate. Objective: to review, preventative pathology among kids. Methods: A hospital-based study was carried out among children of 6 months to 5 years of age who satisfied inclusion and exclusion criteria. Complete detailed history, examination and investigations like urine for culture and sensitivity, and radiological investigations were carried out. Results: Out of total no. of sixty cases sent for piss culture, forty four cases were culture positive. E. coli is isolated in thirty two cases (53.3%). enteric bacteria in seven cases (11.6%) and genus Pseudomonas in exactly three cases (5%) and proteus in a pair of cases (3.3%). Out of total no of cases, 60 cases, fifteen cases were conferred with predisposing factors like sac stones in eight cases (13.3) noted on plain X-ray of abdomen, wherever as hydronephrotic changes were seen in seven cases (11.6%). Conclusion: Organism isolated in gift study E. coli (53.3%) was commonest organism isolated, then followed, by enterobacteria, genus Pseudomonas and Proteus.